Beyond economic man: Feminist theory and economics - Ferber, Marianne A.; Nelson, Julie A. (University of Chicago Press, 1993)
An examination of the central tenets of economics from a feminist point of view. The authors suggest that the discipline of economics could be improved by freeing itself from masculine biases, and raise questions about the discipline's objective nature.
Keywords: OFDIG; approches et analyses; discipline; inégalités; point de vue situé; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie